Legal Protection of Personal Data of Electronic Wallet Users Based on Personal Data Protection ACT - Azis, Kevin; Sitompul, Roswita; Isnainul, OK (International Journal of Business, Law, and Education, 2025)
One of the problems with using digital wallets is that data breaches and account breaches often occur which results in the loss of balances of digital wallet users. The Personal Data Protection Law itself was formed in order to protect people who use digital platforms, in this case digital wallets, from acts of breaching personal data and hacking accounts. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object being researched through data or samples and make conclusions that apply to the general public. The data sources used in this research are primary and secondary data and qualitative data analysis which is observations of phenomena obtained from data obtained in the form of written or oral descriptions. The results of this research are that the regulations for the use of electronic wallets that convert the use of cash into electronic money are Bank Indonesia Regulation Number 20/6/PBI/2018 concerning Electronic Money, Protection of personal data in the Personal Data Protection Law includes specific personal data protection. and is general in relation to the use of electronic wallets, so specific data such as financial data is data that is vulnerable to misuse and must be protected when using electronic wallets.